InDev: A software to generate an MVC architecture based on the ER model. Issue 1 (27th September 2021) - Ramírez‐Noriega, Alan; Martínez‐Ramírez, Yobani; Jiménez, Samantha; Soto‐Vega, Jesús; Figueroa‐Pérez, J. Francisco
Abstract: Model‐view‐controller (MVC) design pattern is employed as software architecture. This pattern has the objective of separating the code into three elements, maintaining layers with defined functions. MVC pattern is used to structure and organize code in software development; therefore, it is an important topic in the teaching of software engineering. However, understanding and implementing this design pattern is not easy for students. Therefore, this investigation proposes a Computer Aided Software Engineering tool called inDev, which is capable of generating an application based on an Entity Relationship (ER) diagram, generating the model, the controller, and the view. The student can interact with the system by visualizing the changes produced by the inputs in the ER diagram in the output as the MVC architecture. To test the scope of the project as a teaching strategy, an experiment was designed with a control group and an experimental group. The experimental group that used the application, inDev, showed better results in learning than the control group, which did not use it. The inDev tool proved to be a useful educational tool for dealing with a topic like the MVC design pattern.